A Survey: Wireless Sensor Networks - Umashankar, M. (IJRDO -Journal of Computer Science Engineering, 2017)
Wireless sensor networks consists of inexpensive sensor nodes, each node has continuous sensing capability withlimited communication power. They can be used for several applications such as commercial, civil, and militaryapplications including vehicle tracking, climate monitoring, intelligence, medical, agriculture, etc. Their deploymentin environments disaster areas, earthquake/rubble zones or in military battlegrounds can be seriously affected by anykind of sensor failure or malicious attack/security threats from an enemy. The amount of power carried by the sensoritself is very limited; replacing sensor or sensor battery is a very time-consuming and costly process, in certainapplication environment. Energy efficient operation, channel contention, latency, management, and security of suchnetworks are complex and critical issues that have to be addressed.